1992
DOI: 10.1515/bchm3.1992.373.2.477
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aspartic Proteinase Inhibitors from Potato at the Gene, cDNA and Protein Levels

Abstract: Cloning and characterization of three cDNAs and one gene coding for the aspartic proteinase inhibitor homologues, detection of four protein isoforms and analysis of the gene copy number indicate that in potato aspartic proteinase inhibitors are encoded by a multigene family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Oryzacystatin I (OCI) (Abe et al, 1987) was expressed as s glutathione S-transferase (GST) fusion protein in Escherichia coli strain BL21 (Stratagene) as previously described (Michaud et al, 1994). Aspartyl proteinase inhibitor (API) was purified from potato as previously described (Kreft et al, 1997) and consisted of several isoforms (Ritonja et al, 1990;Barlic-Maganja et al, 1992;Strukelj et al 1992Strukelj et al , 1995Kreft et al, 1997) of potato cathepsin D inhibitor (PDI) (Keilova and Tomasek, 1976b).…”
Section: Methodsmentioning
confidence: 99%
“…Oryzacystatin I (OCI) (Abe et al, 1987) was expressed as s glutathione S-transferase (GST) fusion protein in Escherichia coli strain BL21 (Stratagene) as previously described (Michaud et al, 1994). Aspartyl proteinase inhibitor (API) was purified from potato as previously described (Kreft et al, 1997) and consisted of several isoforms (Ritonja et al, 1990;Barlic-Maganja et al, 1992;Strukelj et al 1992Strukelj et al , 1995Kreft et al, 1997) of potato cathepsin D inhibitor (PDI) (Keilova and Tomasek, 1976b).…”
Section: Methodsmentioning
confidence: 99%
“…Judging from its primary structure, cathepsin D inhibitor (PDI) belongs to the SKTI family [80]. A series of PDI isoforms were subsequently detected [81,82]. Cathepsin D inhibitors similar to PDI were also isolated from the leaves of tomato ( Lycopersicon esculentum L.) [83].…”
Section: Properties Of Proteinase Inhibitorsmentioning
confidence: 99%
“…The specific conformation of the reactive site loop, containing a scissile peptide bond P1-P1Ј, is conserved by a hydrogen bonding network (Onesti et al, 1991). Kunitz-type inhibitors generally have one reactive site, although PIGENI, PCDI, and WCI might have two reactive sites (Shibata et al, 1988;Maganja et al, 1992;Strukelj et al, 1992). Our previous report indicated that PSPI-21 is a double-headed inhibitor.…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…They have been found in plants belonging to diverse taxonomic groups (Garcia-Olmedo et al, 1987;Ishikawa et al, 1994;. Potato tubers contain various Kunitz-type proteinase inhibitors with a wide variety of specificities for target enzymes, such as trypsin and/or chymotrypsin inhibitors (Walsh and Twitchell, 1991;Suh et al, 1991), subtilisin inhibitor (Suh et al, 1991), cathepsin D and trypsin inhibitors (Mares et al, 1989;Strukelj et al, 1992), and papain and/or cathepsin L inhibitor (Krizaj et al, 1993). These proteins belong to a subfamily named the potato Kunitz-type proteinase inhibitor (PKPI) family (Ishikawa et al, 1994).…”
Section: Introductionmentioning
confidence: 99%